Stress: a challenge for caregivers of people with disabilities - Adum Lípari, Mirella Narcisa (2024)
Primary caregivers of people with disabilities are family members, responsible for the daily care and support of a person, facilitating their physical, emotional and social needs. There are factors that trigger physical and mental consequences, generating from minimal situations and becoming significant problems that affect health and your performance as a caregiver. The objective of this study was to measure the stress of caregivers of people with disabilities in the rural communities of the Honorato Vásquez parish of the Santa Ana canton. A quantitative, field study with a descriptive approach was carried out. The sample consisted of 32 caregivers. The data was obtained through the Zarit Caregiver Overload Test, evaluating aspects such as physical health, emotional, social and economic well-being. The results were a mean of 69.91, which indicates that caregivers experienced a high overload, facing a significant level of stress and emotional, physical and social burden due to their responsibilities. Based on these results, psychological support, training, and support services are recommended, even more so in rural areas where there is limited access to health resources and services, social isolation, and fewer opportunities.